Exploring Teachers' Efforts to Develop Students' Interests and Talents in Elementary Schools - Yanti, Felty Wila (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research aims to explore the efforts made by teachers in developing students' interests and talents at school, using a qualitative approach and case studies. Through observations, interviews and document analysis, data was collected from teachers and students involved in the interest and talent development program. The results of the analysis show that there are four main efforts made by teachers, namely creating supportive conditions, developing interest in achievement, increasing student persistence, and implementing differentiated education. Teachers play an active role in motivating, guiding and involving students in various competitions to actualize their interests and talents. These findings provide a new contribution to the understanding of strategies for developing students' interests and talents in the educational environment. The implication of this research is the need for greater support from schools and parents in creating a conducive environment for the development of students' interests and talents. Apart from that, it is also necessary to pay attention to the importance of implementing differentiated education to meet the diverse learning needs of students. Thus, this research provides a more comprehensive view of how teachers can play an effective role in developing students' potential in schools.